2023
DOI: 10.9745/ghsp-d-22-00197
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Motorcycle Crash Injuries on the Public Health System in Kisumu City, Kenya

Abstract: Motorcycle crash injuries were the second most common cause of both emergency department visits and hospital admissions.The findings showed that motorcycle injury cases contributed to greater radiological diagnostic service use, operating theater use for minor and major surgical procedures, and intensive care unit admissions, demonstrating the extent to which motorcycle crashes contribute to increased use of public health system resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 34 publications
4
9
0
Order By: Relevance
“…Head injury was the most common injury from our study cohort, which is at variance with most studies that reported long bone fractures as the most prevalent injury [ 9 , 16 , 17 ], but is in keeping with a recent study conducted in urban Kenya [ 19 ]. This pattern of injury burden may be a consequence of the preponderant motorcycle-car collision mechanism of injury and their association with traumatic brain injury from head-leading impacts [ 20 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Head injury was the most common injury from our study cohort, which is at variance with most studies that reported long bone fractures as the most prevalent injury [ 9 , 16 , 17 ], but is in keeping with a recent study conducted in urban Kenya [ 19 ]. This pattern of injury burden may be a consequence of the preponderant motorcycle-car collision mechanism of injury and their association with traumatic brain injury from head-leading impacts [ 20 ].…”
Section: Discussionsupporting
confidence: 87%
“…Other authors have alluded to the association of late presentation with worse clinical outcomes while reporting additional predictors of mortality, which include older age of the patient, non-use of helmet, hypotension on admission, severe head injury, injury severity (major trauma), low Glasgow Coma Scale score, and need for intensive care unit admission [ 19 , 22 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fractures are reported to destroy the underlying microstructure frameworks that make bone hard and strong to support locomotor activity participation (Sheen et al, 2023). Fractures and spinal cord injuries have significant functional impairments, long-term disability, and morbidity for victims following commercial motorcycle road accidents (Cholo et al, 2023). Stretch, compression, and breaking through the nervous system may lead to a complete or incomplete nerve spinal cord injury with partial or complete loss of motor and sensory function below the level of injury according to the America Spinal Injury Association (ASIA) scale of assessment (Bennet & Emmady, 2020;Kirshblum et al, 2014).…”
Section: Biological Modelmentioning
confidence: 99%
“…Globally, commercial motorcycle road-related injuries are higher in low-and middle-income countries than in developed countries (Cholo et al, 2023). In African countries, especially South Africa and Malawi, the use of commercial motorcycles as a means of transport is linked to traumatic fractures of the long bones that negatively impact one's several aspects of life (Abbas et al, 2023;Singaram & Naidoo, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In United States of America, 81% of motorcycle road related injuries contribute to the five top categories of impairments namely; traumatic brain injury (TBI), other multiple trauma, TBI with fracture and amputation, other orthopedic, and hip/knee joint replacement (Hoseinian et al, 2019), that require injury diagnosis, medical and in-and outpatient rehabilitation cost (Baptistella et al, 2020). In low-and middle-income countries more than 1.35 million people die with more than 50 million reported to have suffered from long life disability due to road traffic accidents including motorcycle traffic injuries annually (Ahmed et al, 2023;Cholo et al, 2023;Khalaf et al, 2023).…”
Section: Introductionmentioning
confidence: 99%